Embryonic and larval development of backcrossed hybrid grouper between TGGG (Epinephelus fuscoguttatus x E. lanceolatus) and giant grouper (E. lanceolatus) - Sari Asfarina Sariat; Ching, Fui Fui; Norfazreena Mohd Faudzi; Shigeharu Senoo (Elsevier, 2023)
This study examined the embryonic and larval development of TGGGxGG, the backcrossed hybrid grouper tiger grouper (TG) x giant grouper (GG) (Epinephelus fuscoguttatus x E. lanceolatus) and giant grouper (E. lanceolatus), including its morphology, sensory organ development, and behavioural changes. A 15 kg matured hybrid grouper TGGG female and an 80 kg male GG were selected. The findings showed fertilization and hatching rate were recorded at 70.65% and 39.51% respectively and egg size was 850 ± 40 μm. Hatching occurred at 16:43 h after fertilization (hAF) under 29.3C◦ and the size of newly hatched larvae was 1.336 ± 0.118 mm and grew up to 11.95 mm at 50 dAH. Larvae initiated its first feeding at 48 hAH. Behaviourally, newly hatched larvae were seen passive with only up-and-down behaviour but drastically shifted to active feeding at 4 dAH onwards. TGGGxGG larvae show positive phototaxis at 48 hAH when their eyes are fully pigmented and positive rheotaxis at 4 d AH when pectoral fins develop. Free neuromast was distributed on the head parts of newly hatched larvae and its number increased linearly with larval growth until 25 dAH. The new backcrossed hybrid TGGGxGG has similar embryogenesis, larval and sensory organ development as other pure and hybrid groupers. However, slow growth was seen in backcrossed TGGGxGG, hence enhancement of its growth should be further examined.